Development of Service Training Model for Sepaktakraw Athletes in DKI Jakarta - Anton Oktaviansyah; Samsudin; Abdul Gani (Universitas Negeri Semarang, 2024)
This study aims to develop an effective and efficient service training model for sepaktakraw athletes in DKI Jakarta. The research method employs Research and Development (R&D) using the Borg and Gall development model, which consists of ten development steps. The research subjects were divided into two groups: a small group (10 athletes from the UNJ Prestasi Sports Club for sepaktakraw) and a large group (30 athletes from Regional Sport Training Center and Student Sports Training Center of DKI Jakarta). The study produced 15 variations of service training models validated by three experts: the coach of Regional Sports Training Center Sepaktakraw DKI Jakarta, the assistant coach of Regional Sports Training Center, and a sepaktakraw expert lecturer from UNJ. Validation results indicated that all models were deemed feasible for implementation. Analysis data using the t-test showed a significant improvement between the pre-test and post-test scores, with t-value = 24.030 > t-table = 1.699 (p = 0.000 < 0.05). The developed training models integrate the use of tools such as balance balls, resistance bands, and PVC pipes, which have proven effective in enhancing athletes’ service skills. Although requiring intensive supervision, these models successfully created training variations that maintained athlete motivation and prevented boredom during the training process.